PTU-085 Exploring consultant physicians' attitudes and beliefs towards barriers to advance care planning and palliative care in end stage liver disease. (17th June 2017) - Gelmon, L; Macken, L; Mason, L; Verma, S
Abstract : Introduction: Liver disease is a major cause of morbidity and mortality – in the United Kingdom it is the third most common cause of premature death. Mortality rates have increased by over 400% since 1970 and continue to rise. Existing literature suggests that communicating the life-limiting nature of end stage liver disease (ESLD) to patients and subsequent referral to palliative care services is lacking. This study aims to explore the attitudes and beliefs of physicians toward ESLD and consider perceived barriers affecting the provision of palliative care. Method: An online survey exploring attitudes and beliefs towards ESLD and perceived barriers to palliative care was sent to consultants within Southeast England. The survey consisted of both open and closed responses. Qualitative results were analysed according to iterative themes and Likert-type responses were tabulated. Results: A total of 16 of 41 (39%) sampled consultants completed the survey, 8 were gastroenterologists; 3 also identified as being hepatologists. Salient themes that emerged included the belief that patients with ESLD are approached differently to those with cancer, physicians feel less confident in managing patients with ESLD compared with other diseases, patients with ESLD do not receive equitable palliative care compared to those with advanced cancer and there is a reluctance amongst physicians to instigate end of life discussions in those with ESLD. Differences in approaches were associated with inadequate understanding of disease progression, lack of disease awareness from both patient and professional perspectives, limited predictability of prognosis, reliance on specialist hepatology teams to initiate prognostic discussions and discomfort with the subject of palliative care in ESLD patients. Conclusion: This formative study provides evidence that consultants feel confident in recognising ESLD yet are less clear on aspects of prognosis and initiation of advance care planning. Despite the small sample size and low response rate, which limits the generalisability of the findings, themes for further exploration emerged, particularly the incongruity between the identification of those with ESLD and influence on practice in terms of further management and palliative care. Additional themes for further development include raising disease awareness among healthcare professionals and patients, improving identification of patients with or at-risk of developing ESLD as well as earlier discussions regarding prognosis and palliative care involvement. Given the rising prevalence of chronic liver disease nationally, addressing the gaps in management and end of life care for this vulnerable cohort is vital. Disclosure of Interest: None Declared